Topological Indices of Pent-Heptagonal Nanosheets via M-Polynomials - Hafiza Bushra Mumtaz; Muhammad Javaid; Hafiz Muhammad Awais; Ebenezer Bonyah (Journal of Mathematics)
The combination of mathematical sciences, physical chemistry, and information sciences leads to a modern field known as cheminformatics. It shows a mathematical relationship between a property and structural attributes of different types of chemicals called quantitative-structures’ activity and qualitative-structures’ property relationships that are utilized to forecast the chemical sciences and biological properties, in the field of engineering and technology. Graph theory has originated a significant usage in the field of physical chemistry and mathematics that is famous as chemical graph theory. The computing of topological indices (TIs) is a new topic of chemical graphs that associates many physiochemical characteristics of the fundamental organic compounds. In this paper, we used the M-polynomial-based TIs such as 1st Zagreb, 2nd Zagreb, modified 2nd Zagreb, symmetric division deg, general Randi c´, inverse sum, harmonic, and augmented indices to study the chemical structures of pent-heptagonal nanosheets of VC5C7 and HC5C7. An estimation among the computed TIs with the help of numerical results is also presented.